Determination of The Active Asiaticoside Content in Centella asiatica as Anti-Cellulite Agent - Sondari, Dewi; Harmami, Sri Budi; Ghozali, M; Randy, Ahmad; S, Athanasia Amanda; Irawan, Yan (Indonesian Research Gateway, 2011)
CentellaÃÂ asiaticaÃÂ accumulatesÃÂ largeÃÂ quantitiesÃÂ ofÃÂ pentacyclicÃÂ triterpenoid saponins,ÃÂ collectivelyÃÂ knownÃÂ asÃÂ centelloids.ÃÂ TheseÃÂ terpenoidsÃÂ includeÃÂ asiaticoside, centelloside,ÃÂ madecassoside,ÃÂ brahmoside,ÃÂ brahminoside,ÃÂ thankuniside,ÃÂ sceffoleoside, centellose, asiatic-, brahmic-, centellic- and madecassic acids. Preparations of C. asiatica areÃÂ usedÃÂ inÃÂ traditionalÃÂ andÃÂ alternativeÃÂ medicineÃÂ dueÃÂ toÃÂ theÃÂ wideÃÂ spectrumÃÂ of pharmacologicalÃÂ activitiesÃÂ associatedÃÂ withÃÂ theseÃÂ secondaryÃÂ metabolites,ÃÂ suchÃÂ as anticellulite agent. Asiaticoside was found in Centella asiatica. In this present study, the asiaticoside was extracted using methanolic and ethanolic solvent. Determination of the asiaticosideÃÂ contentÃÂ inÃÂ theÃÂ extractÃÂ wasÃÂ conductedÃÂ withÃÂ High PerformanceÃÂ Liquid Chromatography (HPLC), Thin Layer Chromatography (TLC), and Fourier Transform Infra Red (FTIR). Samples of C.ÃÂ asiatica used in this study came from three different plantationÃÂ areas,ÃÂ Bogor,ÃÂ LembangÃÂ andÃÂ Solo.ÃÂ AsiaticosideÃÂ contentÃÂ inÃÂ theÃÂ methanolic extractÃÂ fromÃÂ Bogor,ÃÂ Lembang,ÃÂ andÃÂ SoloÃÂ samplesÃÂ wereÃÂ 2.82%;ÃÂ 2.68%;ÃÂ andÃÂ 2.8% respectively. Asiaticoside in ethanolic extract from Bogor, Lembang, and Solo samples were 2.79%; 2.75%; and 2.91% respectively. Two way ANOVA study showed that there wasÃÂ significantÃÂ differenceÃÂ betweenÃÂ typesÃÂ ofÃÂ solventÃÂ usedÃÂ inÃÂ extractionÃÂ andÃÂ the asiaticosideÃÂ contentÃÂ inÃÂ theÃÂ obtainedÃÂ extract,ÃÂ significantÃÂ differenceÃÂ betweenÃÂ varied plantation area and obtained asiaticoside content, and significant difference between interactions of different solvent with different plantation area.ÃÂ ÃÂ ÃÂ Key words: Centella asiatica, asiaticoside, anticellulite, medicine, metabolitesÃÂ ÃÂ